Tackling Single-Use-Plastic in small touristic islands to reduce marine litter: co-identifying the best mix of policy interventions - Guittard, Alice; Akinsete, Ebun; Demian, Elias; Koundouri, Phoebe; Papadaki, Lydia; Tombrou, Xenia (Frontiers in Environmental Economics, 2023)
Marine litter is a worldwide issue affecting local communities with increasing environmental and economic impacts, with Single-Use-Plastic (SUP) pollution being of specific concern. The tourism industry has been identified as one of the major sector contributing to marine plastic pollution therefor in need to take urgent actions. Small islands are particularly vulnerable and need locally adapted strategies to effectively tackle this issue. This study proposes the use of a participative system-based approach to co-design, with local stakeholders, a roadmap tackling Single-Use-Plastic (SUP) in the hospitality industry of small Greek touristic islands. Policy, industry, civil society and academia representatives were involved in a participative co-creation process to co-identify the best mix of policy instruments and innovations (social and technological) adapted to the local island context, capable of reducing plastic consumption and littering in the island while fostering behavioural change (from consumers and local businesses perspective). Results show the lack of knowledge and awareness, the limited financial resources and expertise, and the low efficiency of the waste management system as the main challenges. A roadmap of short and mid-term actions, based on the Circular Economy reduce, reuse, recycle principles was co-developed, including raising awareness campaigns across stakeholder groups, positive economic incentives, development of capacity building and partnerships within the quadruple helix (academia, business, public authorities and civil society representatives), forming the basis of the municipal island free SUP strategy. The active involvement of public and private actors as well as the civil society, empowering local actors and developing trust across stakeholder groups are key factors to develop a successful strategy able to tackle plastic pollution locally. Pilot experiments also proved to be a determinant for the adoption of sustainable solutions in the context of small islands.